2022
DOI: 10.3389/fvets.2022.814562
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Feedback Loops in the Caprine Circadian Clock System

Abstract: The circadian clock system is based on interlocked positive and negative transcriptional and translational feedback loops of core clock genes and their encoded proteins. The mammalian circadian clock system has been extensively investigated using mouse models, but has been poorly investigated in diurnal ruminants. In this study, goat embryonic fibroblasts (GEFs) were isolated and used as a cell model to elucidate the caprine circadian clock system. Real-time quantitative PCR analysis showed that several clock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Meanwhile, sleep deprivation in the second half of the night has been shown to significantly lower testosterone levels in the morning ( Schmid et al, 2012 ). In addition, relevant animal studies have shown that the steroidogenic-related genes which are responsible for testosterone production in Leydig cells (including Star, Cyp11a1, Cyp17a1, Hsd3b2, Hsd17b3, Sf1, positive-Nur77, and negative-Arr19) also exhibited 24-h rhythmic expression patterns ( Chen et al, 2017 ; Gao et al, 2022 ; Pavlovic et al, 2022 ), And the circadian clock system was involved to the process of bisphenol A ( Li et al, 2021 ) and zearalenone ( Zhao et al, 2021 ) reducing testosterone production. which indicates a crucial role of the circadian clock in testosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, sleep deprivation in the second half of the night has been shown to significantly lower testosterone levels in the morning ( Schmid et al, 2012 ). In addition, relevant animal studies have shown that the steroidogenic-related genes which are responsible for testosterone production in Leydig cells (including Star, Cyp11a1, Cyp17a1, Hsd3b2, Hsd17b3, Sf1, positive-Nur77, and negative-Arr19) also exhibited 24-h rhythmic expression patterns ( Chen et al, 2017 ; Gao et al, 2022 ; Pavlovic et al, 2022 ), And the circadian clock system was involved to the process of bisphenol A ( Li et al, 2021 ) and zearalenone ( Zhao et al, 2021 ) reducing testosterone production. which indicates a crucial role of the circadian clock in testosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, cDNA was generated using a PrimeScript RT Reagent Kit (TaKaRa). All primers were designed to span introns to avoid amplification of genomic DNA, and their availability has been verified in our previous studies [40, 51]. The primer information is presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described [40]. Briefly, GTCs were seeded onto coverslips in 24-well plates and rinsed twice with PBS for 5 min.…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%